Evaluation of Obsessive-Compulsive Disorder Patients According to Gender Differences - Ebru Altintas; Gamze Ozcurumez (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2015)
Purpose: A homogenous classification cannot be obtained because of Obsessive Compulsive Disorder's (OCD) heterogeneous structure. The present study aimed to determine the relation of gender related differences with clinical features, symptom dimensions, age of onset, comorbidity in OCD patients. As distinct from the other studies we also aimed to evaluate the difference of Yale-Brown Obsessive Compulsive Scale's (Y-BOCS) subscales (insight, avoidance, pathologic doubt and pathologic responsibility, instability, retardation) between male and female patients with OCD. Method: The present study comprised of 198 patients aged between 15 and 65 years, who met the OCD criteria of DSM-IV-TR. Detailed data on clinical and sociodemographic characteristics were recorded. The patients were divided into two groups; male (n=65) and female (n=133). The patients underwent Structured Clinical Interview for DSM-IV Inventory (SCID-I), Yale- Brown Obsessive Compulsive Scale and Check List, Beck Anxiety Inventory, Beck Depression Inventory. Scores of these inventories were statistically compared. Results: There were no statistically significant differences in mean age, marital status, education level, family history, social support, hospitalization and suicidal attempt history between the two groups. We found a high treatment seeking, earlier age onset of obsessive-compulsive (OC) symptoms and disorder in males. We did not find any symptom differences except sexual obsession and repeating compulsion between male and female patients with OCD. We also found high BAI and BDI scores in females. We did not find statistically significant differences in the proportion of comorbid psychiatric disorders and the subscales of Y-BOCS between genders. Conclusion: The present study suggests that age of onset, treatment seeking, anxiety, depression level, and some OC symptoms are different between male and female patients and gender may be used for the classification of the OCD. [Cukurova Med J 2015; 40(3.000): 409-417]